Effect of Adipic Acid Composition on Structural and Conductivity Solid Biopolymer Electrolytes Based on Carboxy Methylcellulose Studies - M.L.H. Rozali; N.H. Ahmad; M.I.N. Isa (American-Eurasian Network for Scientific Information publisher, 2024)
Volume :9 Number: 2